Pengaruh Perlakuan Implantasi Hidrogen terhadap Sifat Struktur Lapisan Tipis Amorf Silikon Karbon (a-SiC:H) Hasil Deposisi Metode DC Sputtering - Rosari Saleh; Lusitra Munisa (Institut Teknologi Bandung, 2003)
Infrared absorption measurement of hydrogenated amorphous silicon carbon films (a-SiC:H) deposited by dc sputtering method have been performed for prior- and after hydrogen implantation. The films were deposited by silicon target in argon and methane gas mixtures. The results suggest that both 720 and 780 cm-1 absorption are due to Si-C stretching mode and the transition of the absorption from 2000 to 2100 cm-1 as the methane flow rate increase is not due to a change in carbon concentration, but rather to the formation of voids as supported by hydrogen effusion experiment results.